Anais Dos Workshops Do VI Congresso Brasileiro De Informática Na Educação (CBIE 2017) 2017
DOI: 10.5753/cbie.wcbie.2017.992
|View full text |Cite
|
Sign up to set email alerts
|

Um Estudo Exploratório da Aplicação de Pensamento Computacional Baseado nas Perspectivas de Professores do Ensino Médio

Abstract: Abstract. This paper aims to know the perception of computational thinking abilities by teachers. We carried out a survey and interviews IntroduçãoOs impactos causados pela tecnologia na sociedade fizeram requerer da escola muito mais do que o ensino de conteúdos. A fez repensar como trabalhar diversas competências que são exigidas neste século, entre elas, as competências relacionadas à computação. Blinkstein (2008) acredita que a lista de habilidades exigidas para este século é bem extensa. Porém, ele enfati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…This need is also mentioned by Costa et al [10] and Leite et al [22], who performed interviews with schoolteachers, and concluded that CT abilities and concepts were little understood and little explored in teaching practices.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 90%
See 3 more Smart Citations
“…This need is also mentioned by Costa et al [10] and Leite et al [22], who performed interviews with schoolteachers, and concluded that CT abilities and concepts were little understood and little explored in teaching practices.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 90%
“…Some years after Wing's seminal article in 2006 [35], research in CT in education boomed in Brazil (Figure 1). A manual search in the proceedings of the four main national forums in technologies for learning and computing education (SBIE, WIE, WEI and WAlgProg) shows that the first post-2006 appearance of "computational thinking 10 " in a paper title was in 2012, in the 7 Available at: guiaedutec.com.br/educador (accessed in October 2020) 8 https://launchcs.thinkific.com/courses/computational-thinking-integration-BYOD 9 https://studio.code.org/courses?view=teacher 10 The search was conducted in Portuguese with the terms: "pensamento computacional" (computational thinking) and "raciocínio computacional" (computational reasoning)…”
Section: Academic Research In Brazil On Computational Thinking and Tementioning
confidence: 99%
See 2 more Smart Citations
“…The paper was published in the proceedings of the Workshop on Computing Education (WEI), which, curiously, has not published any other papers on CT and teacher education ever since (Table 1). From the 13 papers retrieved in our manual search on CT and teacher development, 8 present research with teachers in-service (Barcelos, Bortoletto, & Andrioli, 2016;Barros et al, 2018;Costa et al, 2017;Leite et al, 2017;Martinelli, Zaina & Sakata, 2018;Silva, Silva, & França, 2017;Souza, Rodrigues, & Andrade, 2019), and 5 developed research in teacher education programs (preservice) (Barbosa, 2019;Farias, Andrade, & Alencar, 2015;França et al, 2014;França & Tedesco, 2017;Kampff et al, 2016) (Table 1). This is consonant with the international literature of the field, where the number of studies on preservice teacher education involving CT is much lower than in-service (Li, 2021).…”
Section: Academic Research In Brazil On Computational Thinking and Teacher Educationmentioning
confidence: 99%